Impact of Malnutrition on Prognosis in Patients with HER2-negative Metastatic Gastric Cancer - TOPÇU, Atakan; TOPÇU, ATAKAN; YASİN, Ayşe İrem; YASİN, AYŞE İREM (My University, 2022)
Objective: Malnutrition is common in patients with gastric cancer and may adversely affect their prognosis. This study investigated the impact of malnutrition on overall survival (OS) in patients with metastatic gastric cancer by computing the Malnutrition Universal Screening Tool (MUST), one of the most used nutritional screening tools.